Teacher Strategies in Enhancing Quranic Memorization and Psychological Implications for Quranic Memorizers: A Study at Mukhtar Syafa'at Banyuwangi's Distinguished Junior High School - Makrus, Ali; Usriyah, Lailatul (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2023)
In the practical implementation of enhancing Quranic memorization in various schools, there are challenges involved in selecting and implementing effective strategies. Some teachers may encounter difficulties in applying suitable strategies for teaching Quranic memorization, evident in students' struggles with memorization. This study aims to explore how tahfidz teachers at Mukhtar Syafa'at Banyuwangi Distinguished Junior High School employ strategies to improve Quranic memorization, identify factors that either support or hinder these strategies, and describe the psychological implications experienced by Quranic memorizers at the school. The research utilized a qualitative approach with a case study design. The key findings are as follows: Firstly, teacher strategies for enhancing students' memorization involve classical approaches such as repetition, deposits, and simultaneous memorization. Monthly activities encompass memorization competitions, participation in events, annual programs like pilgrimage visits and tahfidz graduations, and a holiday initiative where groups memorize one juz in a day. Secondly, hindering factors include economic difficulties, broken families, lack of enthusiasm, a lack of self-motivation, and laziness. Supporting factors comprise age, students' intelligence, talents and interests, self-motivation, the environment, teachers, friends, and rewards. Thirdly, psychological implications for Quranic memorizers involve strict self-preparation and management, the obligation to maintain memorization, comprehension of the memorized recitations, and the responsibility for their implementation.